Cardiac tamponade as a late complication of a minor trauma due to syncope: A case report and literature review. Issue 2 (March 2020) - Guarino, Matteo; Bologna, Alessandra; De Giorgi, Alfredo; Spampinato, Michele D; Molino, Christian; Gozzi, Dario; Tonelli, Laura; Fabbian, Fabio; Strada, Andrea; De Giorgio, Roberto
Haemopericardium with cardiac tamponade following minor blunt trauma is a rare, life-threatening condition. The diagnosis of cardiac tamponade as well as therapeutic management may be delayed, since the link between trauma and illness is often overlooked. We report the case of an old woman who developed a relatively delayed cardiac tamponade due to an otherwise minor blunt chest trauma following syncope.